Tenun Pahang Diraja: Pride of the Malay heritage / Zuraini Yaacob, Khamizatul Baizura Idris and Faiza Rostam Affendi - Yaacob, Zuraini; Idris, Khamizatul Baizura; Affendi, Faiza Rostam (2023)
Local assets, whether environmental or cultural in nature have become prerequisites for the development of the tourism sector. When it becomes the primary reason for tourists to visit a destination, it shows that the factor is important in tourism especially in countries with a lot of attractions and natural resources. Pahang is one of the states that has a cultural asset i.e. Tenun Pahang Diraja (TPD) that can be used as a tourist attraction in this context. The question is how to transform this valuable craft which is commonly regarded as a mere legacy into something that can provide tourists with experience and uniqueness. Although TPD has been around for decades as an attraction in the tourism sector, there is still room and justification to empower it if this asset is viewed in a more interesting way, providing the authentic local experiences and insights that the tourists of today are looking for.